Pathogenesis, Clinical Presentations and Diagnosis of IgG4-related Disease: A Review - Perdana Aditya Rahman; Cesarius Singgih Wahono; Fajar Maulana Raharjo; Handono Kalim; Mokhamad Fahmi Rizki Syaban (Indonesian Rheumatology Association, 2022)
IgG4-Related Disease (IgG4RD) was identified by the International Classification of Diseases (ICD) in 2012. Numerous diseases, including Mikulicz’s disease, Kuttner’s tumor, Riedel’s thyroiditis, and Ormond’s disease, are pathologically associated with IgG4. Here, we present a review of the clinical presentation and pathogenesis of IgG4-associated disease. IgG4-RD term has been used to refer to a group of diseases involving multiple organs in which there is an abundant IgG4-positive lymphoplasmacytic infiltration, storiform fibrosis, obliterative phlebitis, and mild to moderate tissue eosinophilia, all of which show clinically as a tumefactive lesion, usually in more than one organ. IgG4 exhibits a unique property called an unstable disulfide bond between its heavy chain, as described by Fab-arm exchange which enables the recombination of a single IgG4 heavy chain with other IgG4 heavy chains, resulting in a bispecific antibody incapable of cross-linking and thus of forming an immune complex. IgG4-RD pathomechanism that causes serum IgG4 increase and tissue IgG4-plasma-cell deposition that is pathogenic, rather than the IgG4 itself. Genetic predisposition, autoimmunity, T-cell dysregulation, infection, and dysbiosis are just a few of the underlying pathomechanisms. Clinical symptoms are also frequently complex and may involve many organs. Confirmation of a diagnosis required a comprehensive anamnesis and examination.